Reparixina, um antagonista de CXCR1 e CXCR2, na laminite experimental de equinos - Leonardo Rodrigues de Lima (2013)
Leucocytes recruitment to tissues is an essential part of the innate immune response and an unregulated process can result in tissue damage. Thus, leucocytes infiltration has been implicated in the pathogenesis of acute laminitis. The objectives of this study were to determine the tolerance of horses to the intravenous infusion of reparaxin, an antagonist for CXCR1/2 (achemokine receptor for neutrophils attraction) and these effects on the clinical signs and hematological parameters in horses given oligofructose to induce endotoxemia and laminitis. 30 Twelve horses were given oligofructose (10g/kg bw PO) in time 0 and divided in two groups: treated (30 mg/kg bw. Reparaxin IV, times 6, 12, 18 e 24 h) and no treated. Cardiac andrespiratory frequency, rectal temperature, mucous membrane colour, digital pulse, hoof sensitivity and Obels grade of lameness were recorded. Values for RBC, WBC, glicosis, BUN, creatinin, ALT, AST, alcalin phosphatase, GGT, total bilirrubin and serum protein were measured on times 0, 6, 12, 18, 24, 36, 48, 60 e 72 h. All the horses given oligofructose developed signs ofendotoxemia like diarrhea, fever and leukocytosis. Also, CXCR1/2 antagonist treatment did not cause any adverse effects. However, this substance when injected intravenously (30mg/kg) 6/6 hours for 4 applications, did not ameliorate clinical and hematological signs of endotoxemia. Further studies using hoof biopsies are granted to test a possible beneficial effect in lamellartissue.